2006
DOI: 10.5650/jos.55.249
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Photoinduced by Cosmetic Pigments and Sunscreen Agents under Solar Exposure and Artificial UV Illumination

Abstract: Nanostructured ZnO particles present in skin-care cosmetics and UVB/UVA sunscreen products generate strong oxidizing species (free radicals) when illuminated with UV radiation that can damages human skin and the horny layer. Damage to DNA by ZnO and other pigmentary ingredients in sunscreen formulations under artificial and solar UV exposure has been examined by Agarose gel electrophoresis using pUC 18 DNA plasmids (2686 base-pairs). Initial photoinduced oxidative damage done to DNA plasmids have been probed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…As an only example, Hidaka et al have reported that photo-deformation of DNA plasmids depends on photocatalytic activity of coexisted oxide semiconductors (ZnO, TiO 2 , CeO 2 ). 25) They confirmed that the undoped and doped CeO 2 had little influence on the DNA damage, but the defensive action of CeO 2 was not mentioned. The present paper demonstrates that the photochemically produced CeO 2 nanoparticles effectively reduce the oxidation rate of DNA due both to the ROS scavenging and UV-light shielding abilities.…”
Section: )7)mentioning
confidence: 98%
“…As an only example, Hidaka et al have reported that photo-deformation of DNA plasmids depends on photocatalytic activity of coexisted oxide semiconductors (ZnO, TiO 2 , CeO 2 ). 25) They confirmed that the undoped and doped CeO 2 had little influence on the DNA damage, but the defensive action of CeO 2 was not mentioned. The present paper demonstrates that the photochemically produced CeO 2 nanoparticles effectively reduce the oxidation rate of DNA due both to the ROS scavenging and UV-light shielding abilities.…”
Section: )7)mentioning
confidence: 98%
“…In their study, chromatid gaps and chromatid breaks were observed. Hidaka et al (2006) studied the damage of ZnO and various nanoparticles exposed to UV on plasmid DNA via gel electrophoresis method, and demonstrated that ZnO caused faster and larger DNA damage. Dufour et al (2006) studied the effects of ZnO on Chinese hamsters ovary (CHO) cells.…”
Section: Discussionmentioning
confidence: 99%
“…The UV-A radiation (320-400 nm) is the main component of sunlight causing tanning, actinic premature skin aging, dryness and exfoliation and dermatological photosensitivity of the skin and has been implicated in structural and cellular and skin damage [1][2][3][4] . On the other hand, the UV-B radiation (290-320 nm) contributes significantly to erythema and skin cancer 4) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these pigments are also well-known semiconductor photocatalysts having bandgap energies of 3.2 eV (absorption edge, 387 nm) for TiO 2 anatase and ZnO, and 3.0 eV (414 nm) for TiO 2 rutile. These pigments can generate harmful reactive oxygen species such as O 2 -, HOO and OH radicals when subjected to UV-A/UV-B radiation 2) . Accordingly, these species can cause severe damage of the DNA through strand breaks, as reported in several studies [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation